2020
DOI: 10.1007/s11787-020-00255-0
|View full text |Cite
|
Sign up to set email alerts
|

Farewell to Suppression-Freedom

Abstract: and onward that the variable sharing property is but a mere consequence of a good entailment relation, indeed they viewed it as a mere negative test of adequacy of such a relation, the property itself being a rather philosophically barren concept. Such a relation is rather to be analyzed as a sufficiency relation free of any form of premise suppression. Suppression of premises, therefore, gained center stage. Despite this, however, no serious attempt was ever made at analyzing the concept. This paper shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Once one moves beyond FDE to the full relevant logics, it is not clear that suppression‐freedom is equivalent to sufficiency. Øgaard (2020) provides a natural way of formalizing suppression‐freedom in terms of the two principles 34 Anti‐Suppressive Principle : For every formula A , there are formulas B and C such that ( A ∧ B ) → C is valid but B → C is not. Joint Force Principle : For every formula A , there are formulas B and C such that ( A ∧ B ) → C is valid while neither A → C nor B → C is.…”
Section: Sufficiencymentioning
confidence: 99%
“…Once one moves beyond FDE to the full relevant logics, it is not clear that suppression‐freedom is equivalent to sufficiency. Øgaard (2020) provides a natural way of formalizing suppression‐freedom in terms of the two principles 34 Anti‐Suppressive Principle : For every formula A , there are formulas B and C such that ( A ∧ B ) → C is valid but B → C is not. Joint Force Principle : For every formula A , there are formulas B and C such that ( A ∧ B ) → C is valid while neither A → C nor B → C is.…”
Section: Sufficiencymentioning
confidence: 99%
“…Plumwood's formal suppression-principles-the Anti-Suppression Principle and the Joint Force Principle-were analyzed in [16] where it was shown that these formal principles are in fact properly weaker than the variable sharing property. 1 This paper shows first of all that Plumwood's suppression principles are equivalent to principles motivated by one of Ackermann's motivational spins on his notion of rigorous implication.…”
Section: Introductionmentioning
confidence: 99%
“…1 This paper shows first of all that Plumwood's suppression principles are equivalent to principles motivated by one of Ackermann's motivational spins on his notion of rigorous implication. Even though the formal suppression principles used in [16] turn out to be too weak to do the job they were thought to do, it could be that tweaking the principles slightly would be sufficient to rectify this. [16] did not explore any such tweaked principles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the resulting technical detail "[light] is cast on, and sometimes solutions delivered for, a number of other linked problems". 15 For example, "paradoxes of commitment", so-called Good Samaritan paradoxes and Robber paradoxes. 16 Other paraconsistent approaches to moral dilemmas soon followed.…”
mentioning
confidence: 99%